An exploration of mercaptopurine/methotrexate tolerance during maintenance therapy in children with acute lymphoblastic leukemia. (October 2021) - Whiley, AC; Price, V; MacDonald, T
Purpose: Mercaptopurine (6MP) and methotrexate (MTX) cause myelosuppression and interruptions in therapy in children with lymphoblastic leukemia (ALL). Length of time off of therapy is related to poorer outcomes. To date the dose at which most children tolerate these agents without drops in blood counts has not been identified. This study attempts to determine the maximum tolerated dose of both 6MP/MTX. Methods: A retrospective chart review of 77 ALL children, median age 4.5 years. Time to first interruption and dose, along with total number of interruptions were collected. Absolute neutrophil and platelet counts recorded at time of interruption. Subgroup analysis of age, sex, diagnosis and risk stratification were also completed. REB approval was gained. Results: Of the 77 patients that were studied, 9 of them had no treatment interruptions. Descriptive statistics are reported using Strata software. The mean number of interruptions during maintenance was 3.2, the mean time to first interruption was 149.8 days. The mean dose percent of MTX and 6MP at first interruption was 94.4% and 106% respectively. Maintenance therapy was interrupted independent of age, sex, diagnosis or disease risk stratification. Conclusion: Few patients complete maintenance therapy without interruptions at the current dose escalation schedules outlined by the Children's Oncology Group protocols. The interruptions are due in part to intolerance of dose escalations of MTX and 6 MP above 100%. Future research should investigate doses of 6MP and MTX in maintenance therapy in relation to leukemia outcomes.